Housing Improvement Using Quality Function Development In Melaka Resident Area:A Case Study - Salim, Mohd Azli; Wan Mohamad, Wan Mohd Farid; Maksom, Zulisman; Kamat, Seri Rahayu; Sukarma, Lukman; Putra, Azma; Abdullah, Mohd Azman (Penerbit Akademia Baru, 2014)
This paper presents the housing improvement proposition in the Melaka resident area.Quality Function Deployment is used as a method to analyze customer behavior regarding customer requirement,satisfaction and comparison among the developers.By using this method,the main requirement by the buyer for their bungalow is their need of sufficient space to place their appliances in the house.At the end of the study,the details of buyer requirements are plotted into House of Quality,where it is believed to improve the quality of future bungalow house development in Melaka.